Accuracy assessment of fringe projection profilometry and digital image correlation techniques for three-dimensional shape measurements. (5th January 2021) - Nguyen, Hieu; Liang, Jiali; Wang, Yuzeng; Wang, Zhaoyang
Abstract: With ever-increasing demand for three-dimensional (3D) imaging and shape measurements in a variety of fields, measurement accuracy has become of vital importance to numerous scientific and engineering applications. This paper presents an experimental investigation into the accuracy comparison of two prevalent 3D imaging and shape measurement methods: fringe projection profilometry (FPP) and 3D digital image correlation (3D-DIC) techniques. A detailed description of their principles reveals their inherent similarities and fundamental differences. A measurement system composed of both techniques is employed in the study, and a test target with speckle checkerboard patterns on its surface is adopted to allow simultaneous FPP and 3D-DIC measurements. The evaluation puts emphasis on how the geometric angles between key hardware components affect the 3D measurement accuracy. Experiments show that the depth and height measurements of both techniques can reach sub-micron accuracy, and the relative accuracy of the 3D shape or position measurements can reach 1/600 000.